Sikap Komuniti Setinggan Tebingan Sungai:Pencemaran Alam Sekitar dan Pengurusannya: River Bank Squater Community Attitudes: EnvironmentalPollution and its Management - Ismail, Hamidi; Syed Hussain, Tuan Pah Rokiah; Mariyappan, Raman (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2011)
The attitudes of river bank squatter communities and its relationship to surface water contamination is an issue that has never been over. This article discusses two basic aspects: firstly the river bank squatter communities attitudes and relationship with the river pollution and secondly, the management needs to reduce river pollution by the community. This paper briefly review issues based on published articles. This paper views that the squatter attitude have always been problems in managing the river and it’s surrounding. This is evident clearly showed that the squatter communities pollute the river and by the same time challenging the state legislation or the government. Their attitude is thus preventing the government efforts in environmental management. Failures in existing management system which only emphasizes the role of government in managing the development in order to change the paradigm of environmental change management design towards good management practice by serious involvement or cooperation by all parties in the government and to be fully supported by the communities, private sectors and non-governmental organizations (NGOs).